Impact of introducing transnasal endoscopy on expanding diagnostic endoscopy services - Nigel Trudgill; Hasan Haboubi; Jeff Turner; Laura Munglani; Tom Crosby; Ben Thomas Crosby; Karen Wright; Kay Charles; Wendy Evans; Megan Mathias; Stevie Davies; Badr Abdalla (BMJ Open Quality)
Introduction Demand for endoscopic services is outstripping capacity in the UK. Transnasal endoscopy (TNE) utilises a narrow calibre endoscope to pass through the nasal passages, thereby reducing retching and discomfort. It is better tolerated compared with standard transoral endoscopy (TOE) but is still rarely used as a diagnostic modality. There is still uncertainty about how well it performs against TOE in diagnostic ability, cost and efficiency.Methods We explored utilising TNE to deal with the growing demand for endoscopy. We compared findings to TOE procedures undertaken during the same time period. We evaluated cost differences, duration/time in the department for procedures as well as quality of procedures (both in terms of performance indicators as well as image quality using the validated POLPREP score).Results A total of 241 upper gastrointestinal endoscopy procedures were evaluated (100 TNE and 141 matched TOE) between December 2021 and February 2022. TNE outperformed TOE in obtaining >95% success rate in nationally approved key performance indicators (retroflexion and duodenal intubation, both p=0.026). It also was associated with better image quality in the oesophagus with a POLPREP A3 Score (excellent image quality) in 36/98 available images compared with 26/136 TOE (p=0.028) and was equivalent to TOE in the stomach and duodenum. TNE was identified as having a key role in facilitating complex cases, previously failed via the TOE route with a success rate in 11/12 (91.7%) of such cases. TNE also shows promise in correcting misdiagnoses of short-segment Barrett’s oesophagus (39%) compared with TOE (14.8%) (p=0.087).Conclusion TNE is an emerging endoscopic modality, which shows great promise in replacing TOE in most diagnostic circumstances. In a modern healthcare service, TNE is cheaper, better tolerated and outperforms TOE in multiple domains.